The first patients treated with MR-CBCT soft-tissue matching in a MR-only prostate radiotherapy pathway. Issue 2 (March 2023) - Wyatt, J.J.; Pearson, R.A.; Frew, J.; Walker, C.; Richmond, N.; Wilkinson, M.; Wilkes, K.; Driver, S.; West, S.; Karen, P.; Brooks-Pearson, R.L.; Ainslie, D.; et al.
Abstract: Introduction: Magnetic Resonance (MR)-only radiotherapy for prostate cancer has previously been reported using fiducial markers for on-treatment verification. MR-Cone Beam Computed Tomography (CBCT) soft-tissue matching does not require invasive fiducial markers and enables MR-only treatments to other pelvic cancers. This study evaluated the first clinical implementation of MR-only prostate radiotherapy using MR-CBCT soft-tissue matching. Methods: Twenty prostate patients were treated with MR-only radiotherapy using a synthetic (s)CT-optimised plan with MR-CBCT soft-tissue matching. Two MR sequences were acquired: small Field Of View (FOV) for target delineation and large FOV for organs at risk delineation, sCT generation and on-treatment verification. Patients also received a CT for validation. The prostate was independently contoured on the small FOV MR, copied to the registered CT and modified if there were MR-CT soft-tissue alignment differences (MR-CT volume). This was compared to the MR-only volume with a paired t-test. The treatment plan was recalculated on CT and the doses compared. Independent offline CT-CBCT matches for 5/20 fractions were performed by three therapeutic radiographers using the MR-only contours and compared to the online MR-CBCT matches using two one-sided paired t-tests for equivalence within ±1 mm. Results: The MR-only volumes were significantly smaller than MR-CT ( p = 0.003), with a volume ratio 0.92 ± 0.02 (mean ± standard error). The sCT isocentre dose difference to CT was 0.2 ± 0.1%. MR-CBCT soft-tissue matching was equivalent to CT-CBCT ( p < 0.001), with differences of 0.1 ± 0.2 mm (vertical), −0.1 ± 0.2 mm (longitudinal) and 0.0 ± 0.1 mm (lateral). Conclusions: MR-only radiotherapy with soft-tissue matching has been successfully clinically implemented. It produced significantly smaller target volumes with high dosimetric and on-treatment matching accuracy. Implications for practice: MR-only prostate radiotherapy can be safely delivered without using invasive fiducial markers. This enables MR-only radiotherapy to be extended to other pelvic cancers where fiducial markers cannot be used.